AB0228 Gas6/tam-system in systemic sclerosis and sjÖgren syndrome: SMER as an indicator of pulmonary hypertension. (23rd January 2014) - Sola, D.; Sainaghi, P.P.; Coccetta, A.; Bellan, M.; Molinari, R.; Nerviani, A.; Pirisi, M.
Abstract : Background: Impaired phagocytosis of apoptotic bodies, inflammation and fibrosis are common features of Systemic Sclerosis (SSc) [1] and Sjögren Syndrome (SS) [2]. The Gas6/TAM-system is involved in all these processes [3, 4]. Objectives: To evaluate plasma Gas6 and sTAM receptors concentrations as putative biomarkers in SSc and SS. Methods: Forty-one consecutive patients with SSc (n.=23) or SS (n.=18) were recruited at a tertiary level rheumatology unit from December 2010 to May 2011; age-matched patients (n.=46) with degenerative joint disease served as controls. Relevant clinical data, including those on immunosuppressive therapies, comorbidities, physical examination, systolic pulmonary artery pressure (PAPs), ESR, CRP, C3, C4, modified Rodnan-skin-score, Valentini-score, Kazerooni-score, anti-centromere and/or anti-scl70 antibody positivity were recorded in a database. Plasma Gas6, sMer, and sAxl concentrations were measured by an ELISA method developed and validated at our laboratory [5] and by commercially available kits (R&D, USA), respectively. Non parametric, Pearson's chi-square and multiple linear regression analyses were performed. Results: Subjects with SSc, SS and controls were similar for age, sex and comorbidities (autoimmune thyroid disease and hypertension) (Kruskaal-Wallis variance p>0.31). Median plasma Gas6 and sAxl were not different between groups (Kruskal-Wallis variance, p>0.05), while median plasma sMer was higher in SSc (3.5 ng/ml, 2.9-4.3 IQR) versus SS (3.3, 2.7-4.8) or controls (2.6, 2.4-3.2); post-hoc analysis p<0.009. At multiple linear regression analysis, plasma sMer correlated with PAPs (β=0.86, p=0.02) and ESR (β=0.18, p=0.05) but not with any other variables. Conclusions: Plasma sMer concentration is higher in SSc patients and associates with pulmonary arterial hypertension, but not with indexes of pulmonary fibrosis or scleroderma disease activity scores. The Gas6/Mer system may be relevant in the pathophysiology of pulmonary hypertension, possibly via the control of endothelial apoptosis. References: N Hunzelmann and J Brinckmann. What are the new milestones in the pathogenesis of systemic sclerosis? Ann Rheum Dis 2010 69: i52-i56 Rehman HU. Sjögren's syndrome. Yonsei Med J 2003 Dec 30;44(6):947-54. Review. Lemke G, Burstyn-Cohen T.TAM receptors and the clearance of apoptotic cells. Ann N Y Acad Sci 2010 Oct;1209:23-9. doi: 10.1111/j.1749-6632.2010.05744.x. Alciato F, Sainaghi PP, Sola D, Castello L, Avanzi GC. Tnf-alpha, IL-6 and IL-1 expression is inhibited by Gas6 in monocytes/macrophages. J Leuk Biol 2010. Sainaghi PP, Alciato F, Carnieletto S, Castello L, Bergamasco L, Sola D, Bongo AS, Inglese E, Polosa R, Avanzi GC. Gas6 evaluation in patients with acute dyspnea due to suspected pulmonary embolism. Respir Med 2009;103:589-94. Disclosure of Interest: None Declared